Maternal euglycemia in gestational diabetes mellitus and intrauterine fetal death : A case report - Yee Yee, Kyaing; Awi, Idi (Malaysian Medical Association, 2022)
ABSTRACT Introduction: Prevalence of diabetes in pregnancy world-wide is 1% to 28% and it is 27% in Malaysia. Since 1909, evidence showed that diabetes in pregnancy had high perinatal mortality. Case Description: A 35-year-old Gravida 2 Parity1 booked antenatal care at 9 weeks of pregnancy. Previous pregnancy was delivered by caesarean section indicated with unstable lie. Her booking antenatal investigations were normal as well as protein and sugar were absent in her urine protein. Her BMI was 21.2 Kg/m2. Ultrasound scan at 15-week pregnancy showed fetal biometry measurements consistent with gestational age. At 25 weeks of pregnancy, she was diagnosed with gestational diabetes mellitus as modified oral glucose tolerance test result showed 5.4 mmol/L and 8.5 mmol/L at fasting and 2 hours post prandial respectively. Her 7 points blood sugar monitoring results were satisfactory. At 28 weeks of pregnancy, fetal movement was lost, and intrauterine fetal death was confirmed by ultrasound scan. She was referred to Sarawak General Hospital for further management. Discussion: Maintenance of normal blood sugar level is accepted as a key modifiable factor to reduce adverse perinatal outcomes. Evidence showed that the intrauterine fetal death in diabetes in pregnancy is associated with antenatal risks high body mass index, weight gain during pregnancy and advanced maternal age. But this pregnant lady didn’t have those factors except her age. Causes of intrauterine fetal death in diabetes in pregnancy was still unclear and even in antenatal euglycemia, it would be possible.